First‐line chemoimmunotherapy for patients with small‐cell lung cancer and interstitial lung abnormality: CIP risk and prognostic analysis - Yu Li; Yuxin Jiang; Luyun Pan; Jun Yao; Shuo Liang; Yanjun Du; Dong Wang; Hongbing Liu; Fang Zhang; Qin Wang; Tangfeng Lv; Ping Zhan (Thoracic Cancer)
Abstract Background Patients with non‐small‐cell lung cancer (NSCLC) receiving immunotherapy face a potential risk of developing checkpoint inhibitor‐related pneumonitis (CIP). However, there is no clear understanding of the specific link between interstitial lung abnormality (ILA) and CIP in patients with small‐cell lung cancer (SCLC). In addition, the prognosis of SCLC patients with ILA who receive chemoimmunotherapy is uncertain. Our study aimed to investigate the effect of ILA on the occurrence of CIP in SCLC patients receiving first‐line chemoimmunotherapy and to assess its relationship with prognosis. Methods We conducted a retrospective analysis of SCLC patients who received chemoimmunotherapy as a first‐line treatment between January 2018 and April 2024. The diagnosis of ILA was assessed by two experienced pulmonologists based on pretreatment chest computed tomography images. We investigated independent risk factors for CIP using logistic regression analysis and factors affecting PFS and OS using Cox regression analysis. Results A total of 128 patients with SCLC were included in the study. ILA was present in 41 patients (32.03%), and CIP occurred in 16 patients (12.50%). In multivariate logistic regression analysis, previous ILA (OR, 5.419; 95% CI, 1.574–18.652; p = 0.007) and thoracic radiation therapy (TRT) (OR, 5.259; 95% CI, 1.506–18.365; p = 0.009) were independent risk factors for CIP. ILA (HR, 2.083; 95% CI, 1.179–3.681; p = 0.012) and LDH (HR, 1.002; 95% CI, 1.001–1.002; p < 0.001) were statistically significant for increased mortality risk in multivariate Cox regression analysis. Conclusions In SCLC patients receiving first‐line chemoimmunotherapy, baseline ILA is a risk factor for CIP and is associated with poorer prognosis.